2015
DOI: 10.1007/s00330-015-3809-x
|View full text |Cite
|
Sign up to set email alerts
|

High resolution pituitary gland MRI at 7.0 tesla: a clinical evaluation in Cushing’s disease

Abstract: ObjectiveTo evaluate the detection of pituitary lesions at 7.0 T compared to 1.5 T MRI in 16 patients with clinically and biochemically proven Cushing’s disease.MethodsIn seven patients, no lesion was detected on the initial 1.5 T MRI, and in nine patients it was uncertain whether there was a lesion. Firstly, two readers assessed both 1.5 T and 7.0 T MRI examinations unpaired in a random order for the presence of lesions. Consensus reading with a third neuroradiologist was used to define final lesions in all M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 29 publications
1
29
0
1
Order By: Relevance
“…19 In a later series of healthy subjects (six scanned at 7T, two of which were additionally scanned at 3T), Gizewski et al demonstrated excellent visualization of brain stem structures and exiting nerves at 7T, including structures that were not detectable at 3T, such as the vagal and glossopharyngeal nerves. 18 While de Rotte et al successfully demonstrated imaging of the pituitary gland and chemically confirmed microadenomas with 7T images, 10,12 their studies did not analyze the surrounding cavernous anatomy. To the best of the authors’ knowledge, no previous studies have demonstrated the visualization of the cranial nerves with 7T MRI as they course through the cavernous sinus in neither healthy subjects nor in patients with local pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In a later series of healthy subjects (six scanned at 7T, two of which were additionally scanned at 3T), Gizewski et al demonstrated excellent visualization of brain stem structures and exiting nerves at 7T, including structures that were not detectable at 3T, such as the vagal and glossopharyngeal nerves. 18 While de Rotte et al successfully demonstrated imaging of the pituitary gland and chemically confirmed microadenomas with 7T images, 10,12 their studies did not analyze the surrounding cavernous anatomy. To the best of the authors’ knowledge, no previous studies have demonstrated the visualization of the cranial nerves with 7T MRI as they course through the cavernous sinus in neither healthy subjects nor in patients with local pathology.…”
Section: Discussionmentioning
confidence: 99%
“…35,41 Two studies by De Rotte et al have demonstrated the feasibility of imaging the pituitary gland as well as improved detection of clinically suspected microadenomas at 7T MRI. 12-11 While these studies were the first to demonstrate the feasibility of imaging the pituitary gland and microadenomas at 7T, they did not include 3T images for comparison nor did they include analysis of the surrounding neural and vascular structures of most concern for surgical approaches to the sellar and parasellar spaces.…”
Section: Introductionmentioning
confidence: 99%
“…One remaining prob-lem is very small pituitary adenomas that are impossible to identify using 3-T MRI. In the future, higher magnetic field MRI may resolve this problem [10].…”
Section: Limitations Of the Detectable Tumor Sizementioning
confidence: 99%
“…15 Early reports suggesting feasibility and benefits of ultra-high field MRI over lower field techniques in pituitary pathology have been limited by small sample sizes and inability to statistically compare 7 T to lower field scans. 9,14 Furthermore, the utility of 7 T MRI has not been quantitatively examined in a homogenous cohort of pituitary adenoma patients. The purpose of the present study was to acquire preoperative 7 T MRI and quantitatively compare detailed neuroradiological findings for pituitary adenomas and adjacent skull base neurovascular structures to conventionl MRI.…”
Section: Introductionmentioning
confidence: 99%